Corpos híbridos : o estranho como devir na literatura especulativa - Miranda, Járede Oliver de (2018)
Some narratives of speculative fiction, which present bodies in transformation, are analyzed in this work. Taking as reference the ethnographic method, it is sought to understand how the transformations in the bodies of fictional characters approach or distance themselves from the notion of hybrid bodies, presented by contemporary theorists. In this way, we try to think the transformations in the identities and their senses for the societies where the fiction of the stranger is produced and consumed, as well as in other contexts where the metamorphoses occur, as in narratives of amerindian peoples. The transformations of bodies in the speculative literature appear as metaphors for various processes of transubjectivation in contemporary times. In this context, we find some issues related to gender relations, violence and criticism of the notions of stable identities that mark the discourses of various social groups.